Sensitivity of the particle size determined inline by Photon Density Wave Spectroscopy with respect to sample properties and measurement settings during emulsion copolymerization reactions - Usue Olatz Aspiazu; Sebastian Zimmermann; Marvin Münzberg; Jose Ramon Leiza; Maria Paulis (Polymer Testing)
Photon Density Wave spectroscopy (PDWS) is one of the few real-time and inline submicron particle size monitoring techniques that are commercially available nowadays. In this work, a sensitivity analysis of the PDWS results with respect to relevant sample properties and measurement settings is carried out. It is investigated how the distances between the emission and detection fibers together with the laser modulation frequencies, and uncertainties of the input parameters (refractive index, density, and solids content of the dispersed phase) needed for data analysis affect the reduced scattering coefficients and particle diameters obtained from inline PDWS measurements. The seeded semibatch emulsion copolymerization of methyl methacrylate (MMA, 51 w-%), butyl acrylate (BA, 47 w-%), and methacrylic acid (MAA, 2 w-%) is used as a model system. It is shown that the careful selection of measurement distances and modulation frequencies increases the accuracy of the particle size determination by PDWS. Furthermore, it is observed that the obtained particle sizes are more sensitive to uncertainties of the refractive index and solids content than to uncertainties of the density of the disperse phase.